Uterine Cervix Rhabdomyosarcoma : A Case Report - Sinha, Kavita; Adhikari, Home Nath; Baidya, Pooja (Journal of Nepalgunj Medical College, 2023)
Rhabdomyosarcoma is a malignant tumor that arises from embryonal skeletal muscle cells. It is responsible for 3% of cancer cases among children aged from 0 to 14 and 1% among adolescent and young adult aged from 15 to 19. Embryonal Rhabdomyosarcoma is the most prevalent subtype in the female genital tract and Botryoid sarcomas being a polypoid variant. In young patients, the majority of genital tract rhabdomyosarcomas occur in vagina; however, the most common site being cervix followed by uterine corpus, in adults. We hereby report a case of 24 years lady P2L2 diagnosed as Botryoid Embryonal Rhabdomyosarcoma with evidence of anaplasia without extrauterine metastasis. Embryonal cervical rhabdomyosarcoma is a rare malignant tumor and its typical manifestations are vaginal bleeding and a pelvic mass. However, attention should also be paid to any abnormal vaginal discharge in young unmarried women. Diagnosis of pure rhabdomyosarcoma in uterus involves perfect sampling and histopathological evaluation.